Iniciativas de empleo y apoyos a la creación de nuevas empresas - Alloza, Emilio; Zapatero González, Rafael; Hernando Zulaica, Francisco Javier; Casanova, Carmen; Martínez Laseca, José Luis (Acciones e Investigaciones Sociales, 2013)
Iniciativas de empleo y apoyos a la creación de nuevas empresas